Językowe środki wykluczania. Obraz Romów we współczesnej prasie węgierskiej z perspektywy Krytycznej Analizy Dyskursu - Kozakiewicz, Joanna (Wydział Neofilologii UAM w Poznaniu, 2016)
The present thesis aims to answer a number of critical research questions investigating the relation between press discourse and the position of the Roma minority in Hungarian society. The main research goal was to determine the most important features of the Hungarian press discourse and its practices with regard to the Roma minority. The research data consisted of a corpus of articles collected from three Hungarian newspapers that were published in the twelve-month period between January, 1 and December, 31 2013 and that contained the key words ‘roma’ (Roma) and ‘cigány’ (Gypsy). The newspapers included in the corpus represent different political orientations. The collocation analysis was used to determine the main thematic articulations according to which the Roma are represented in the Hungarian press discourse, while the analysis of concordances, fragments of articles and the use of specific grammatical categories provided a valuable insight into the ways in which exclusionary practices took place. The results were interpreted in the paradigm of Critical Discourse Analysis.
Keywords: Romowie; Cyganie; Romowie na Węgrzech; dyskurs prasowy; Krytyczna Analiza Dyskursu; językoznawstwo korpusowe; Romanies; Gypsies; Roma people in Hungary; press discourse; Critical Discourse Analysis; corpus linguistics